Kim, numéro zéro - Amram, David 1989-; Burns, Charles 1955-; Capron, Jean-Louis 1969-; Claveloux, Nicole 1940-; Cossé, Antoine 1981-; Crabières, Henri; Crumb, R. 1943-; Debeurme, Ludovic 1971-; Dubois, Jérôme 1989-; Ecary, Simon; Maillard, Antoine 1989-; Micol, Hugues 1969-; et al. (Éditions Cornélius, 2023)
Offert pour l'achat des trois premiers numéros de la collection Kim
Offsetdruck(?)
Keywords: Graphzine